Synergic effect in the reduction of serum uric acid level between ethanol extract of Aster glehni and vitamin B6 - Han, Eun Hye; Lim, Mi Kyung; Lee, Sang Ho; Kim, Hyoung Ja; Hwang, Dahyun (Food science and biotechnology, 2018)
In this study, synergistic hypoudpricemic activities between ethanol extract of Aster glehni (AG) and vitamin B 6 were investigated in vitro and in vivo. Xanthine oxidase inhibitory activities in the different parts, leaf, stem, and flower, during spring and autumn were compared. In addition, to improve hypouricemic activity, two chemicals (AG extract and vitamins) were mixed and measured inhibitory activity of xanthine oxidase. As a result, autumn leaf AG extracts showed the most effective xanthine oxidase inhibitory activity and we named autumn leaf AG extracts as AG-D006. In synergistic study, AG-D006 with vitamin B 6 showed significantly increased inhibitory activity on xanthine oxidase. AG-D006 with vitamin B 6 also showed significantly reduced uric acid level in hyperuricemic rats in vivo. In conclusion, AG-D006 with vitamin B 6 might be used functional foods in reducing serum uric acid level in gout.